An examination of the evidence of abrasive wear in the wearing process of aluminium reinforced with slag particles using SEM - Zamri, Yusoff; Shamsul Baharin, Jamaludin, Prof. Dr.; Misbahul, Amin (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.